1998
DOI: 10.1046/j.1365-2648.1998.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological factors on the self‐management of insulin‐dependent diabetes mellitus

Abstract: This study investigated the influence of a number of psychological factors upon the practice and outcome of diabetic self-management among young adults with insulin-dependent diabetes mellitus. Health beliefs, perception of control and knowledge were assessed by scales and questionnaires and glycosylated haemoglobin results and clinic attendance records obtained for 263 patients. The results demonstrated that the sample members perceived that they were responsible for the control of their diabetes, that the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Patients with poor or adequate metabolic control were equally likely to have the same levels of social support as patients who were acceptably controlled, substantiating previous findings on the lack of a relationship between social support and metabolic control (Wilson et al 1986;Coates & Boore 1998;Pouwer et al 2001). However, patients with controlled BP had more social support than patients with poor BP control.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Patients with poor or adequate metabolic control were equally likely to have the same levels of social support as patients who were acceptably controlled, substantiating previous findings on the lack of a relationship between social support and metabolic control (Wilson et al 1986;Coates & Boore 1998;Pouwer et al 2001). However, patients with controlled BP had more social support than patients with poor BP control.…”
Section: Discussionsupporting
confidence: 84%
“…These findings also substantiated previous research on the relationship between support, health, well-being and ethnicity (Shenkel et al 1985;Schwartz et al 1986;Brown & Gary 1987;Littlefield et al 1990;Mengel et al 1990;Belgrave 1991;Walls & Zarit 1991;Belgrave & Lewis 1994;Anderson et al 1996;Coates & Boore 1998;Rubin 2000;Pouwer et al 2001). For African-Americans, social support has been found to promote health and well-being (Brown & Gary 1987), assist with adjustment to disability (Belgrave 1991), play a key role in chronic disease management (Belgrave & Lewis 1994) and maintain well-being among the elderly (Walls & Zarit 1991).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While it is hypothesized that more knowledge about one's condition translates to improved self-care behaviors, there is evidence that patient knowledge may not be directly related to selfmanagement behaviors. 37,39 Previous studies have shown neither knowledge of one's recent A1c level nor high diabetes-related knowledge scores were associated with adherence to diabetes self-care behaviors or 1Ac levels among adults with type 2 diabetes. 37,39 Finally, the association between shorter duration with diabetes, only taking oral medications, and higher medication adherence may be an artifact of the type of medication prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…(Wooldridge et al 1992). Lack of knowledge may affect adherence (Coates & Boore 1998), and the amount of knowledge appears to relate to self-care only among patients with sufficient motivation (Pennings-van der Eerden 1990). Concerning adherence to the prescribed diet, knowledge is needed, but social demands and personal preferences have been found to be play a major role, and simplification of the diet regimens has been recommended (Lo 1998).…”
Section: Diabetes Self-care Practicesmentioning
confidence: 99%